Onward Ho! Studying Place Emotions, Language Style, and Social Tendencies in Travel Blogs - Abdulla, Aleesha; Suresh, Kalyani (Prabandhan: Indian Journal of Management, 2017)
A narrative analysis of the blog posts from Asian countries taken from travelblog.org was conducted in January 2017 in order understand the travel bloggers' emotional experiences, language style, and social tendencies. Tone Analyzer from IBM was used to study emotional dimensions (anger, disgust, fear, joy, and sadness) ; language style dimensions - analytical, confident, tentative ; and social tendency dimensions - openness, conscientiousness, extraversion, agreeableness, and emotional range. The results showed sadness and joy being the predominant emotions expressed in the travel blogs that were studied. Tourists are exposed to both the best and worst things in the places of travel, and so probably, they experience joy and sadness together. Anger was the least expressed emotion. Emotional range topped among social tendencies of bloggers, with a tentative language style being utilized across travel accounts in Asia.